Transient Ipsilateral Hemineglect Following Brain Laser Ablation in Patient with Focal Cortical Dysplasia - Georgios Ntolkeras; Fatemeh Mohammadpour Touserkani; Michelle Y. Chiu; Sanjay P. Prabhu; Scellig Stone; Alexander Rotenberg (MDPI AG, 2024)
Sensory integration is the province of the parietal lobe. The non-dominant hemisphere is responsible for both body sides, while the dominant hemisphere is responsible for the contralateral hemi-body. Furthermore, the posterior cingulate cortex (PCC) participates in a network involved in spatial orientation, attention, and spatial and episodic memory. Laser interstitial thermotherapy (LiTT) is a minimally invasive surgery for focal drug-resistant epilepsy (DRE) that can target deeper brain regions, and thus, region-specific symptoms can emerge. Here, we present an 18-year-old right-handed male with focal DRE who experienced seizures characterized by sensations of déjà vu, staring spells, and language disruption. A comprehensive evaluation localized the seizure focus and revealed a probable focal cortical dysplasia (FCD) in the left posterior cingulate gyrus. The patient underwent uneventful LiTT of the identified lesion. Post-operatively, he developed transient ipsilateral spatial neglect and contralateral sensory loss, as well as acalculia. His sensory symptoms gradually improved after the surgery, and he remained seizure-free after the intervention for at least 10 months (until the time of this writing). This rare case of ipsilateral spatial and visual hemineglect post-LiTT in epilepsy underscores the importance of recognizing atypical neurosurgical outcomes and considering individual variations in brain anatomy and function. Understanding the dynamics of cortical connectivity and handedness, particularly in pediatric epilepsy, may be crucial in anticipating and managing neurocognitive effects following epilepsy surgery.